Design and implementation of a web opac subject browsing guide - Ji, Chunjie (2008)
By prototyping a Web-based subject browsing guide and linking it to a Web-based OPAC, this study investigates how a subject browsing guide should be designed and implemented by utilizing Web and relational database technology.